The Study of The Electrical Conductivity and Activation Energy on Conductive Polymer Materials - Azari, Balqyz Lovelila Hermansyah; Wicaksono, Totok; Damayanti, Jihan Febryan; Azari, Dheananda Fyora Hermansyah (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2021)
Conductive Polymers are one of the interesting topics to be developed in recent years. Conductive polymers can combine the properties of polymers and the electrical properties of metals. Research related to the electrical properties of conductive polymers, including electrical conductivity measurements and determination of activation energy has been carried out. This study aims to determine the effect of addition mass fraction of activated carbon into the nylon polymer on the conductive polymer material based on the electrical conductivity and activation energy. The variations of activated carbon used are 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% (wt/V). The conductive polymer from nylon polymer and activated carbon is made by casting solution method. The electrical conductivity measurement of the conductive polymer and the activation energy was carried out using the parallel plate method. The value of electrical conductivity increased from 5.62×10-9 ± 1.89×10-10 S/cm for the pure nylon to 2.51×10-8 ± 2.87×10-10 S/cm for the addition of mass fraction of activated carbon 8% wt/V. Meanwhile, there was a decrease in the addition of 9% wt/V and 10% wt/V of mass fraction of activated carbon, which were 2.36×10-8 ± 3.47×10-10 S/cm and 2.28×10-8 ± 4.01×10-10 S/cm. The activation energy of conductive polymer obtained decreased with increasing in the mass fraction of the activated carbon into the nylon polymer. The activation energy for the pure nylon was 0.0189 eV and 0.0127 eV for the addition of 8% wt/V mass fraction of activated carbon. Meanwhile, there was an increase in the addition of 9% wt/V and 10% wt/V mass fractions of activated carbon of 0.0145 eV and 0.0150 eV, respectively.